THE RIGHT TO HEALTH AS ONE OF THE MAIN SOCIAL DETERMINANTS OF HEALTH - Michel Perreault; Erica Rios de Carvalho; Fernando P. Cupertino de Barros (Universidade Federal de Santa Maria, 2014)
Doi: http://dx.doi.org/10.5902/2179769213854 In this article, which approaches the Brazilian and the Canadian contexts, the right to Health will be examined as one of the main social determinants of Health. According to the 1988 Constitution, the Sistema Único de Saúde consecrated health as a fundamental right. However, it allowed the private sector to participate as a complement to the public system. Nowadays, one of the main problems is that the private sector isn't complementary to the public, but competes with it thoroughly. There is a debate in Brazil about the assurance of access to health as a fundamental right or the lack of it because of financial inputs beyond the financing capacity of the sector. Ahead of the current paralization of the system, it seems to be a duty of its professionals and managers to develop operational approaches of surveillance of an ethics that is not limited to the Declaration of Free Consent, but as a global Project to look at the Brazilian underdevelopment as an ethical issue.